The accession of Spain to the EEC : negotiations, problems and solutions with special reference to the agricultural sector - Çiftçi, Mehmet (My University, 1989)
unknown
Keywords: Ekonomik Gelişim_Tarım_İspanya; Tarım Politikası_Türkiye